Pengaruh Konsentrasi Rendaman Air Garam Terhadap Kadar Formalin Pada Ikan Asin Formalin is a chemical additive that is efficient, but banned from use in food (foods). But in practice, many manufacturers are using formalin in food, one of which anchovies. - Suharsih Thahir (Jurnal Media Laboran, 2016)
Formalin is a chemical additive that is efficient, but banned from use in food (foods). But in practice, many manufacturers are using formalin in food, one of which anchovies. Anchovies containing formalin aims to maintain the freshness of the product is preserved so that could last long and quickly decay. Formalin can cause cancer if consumed in high doses. Therefore, efforts to reduce the levels of formaldehyde from food such as salted fish so it is relatively safe umtuk consumed The purpose of this study was to determine the effect of the concentration of salt water immersion on levels of formaldehyde in salted fish. This type of research is experimental. The samples used are anchovies marinated snapper formalin by means of the examination conducted by the 3 treatments. From the results of quantitative research conducted at the Center for Health Laboratory Makassar in 2015 found decreased levels of fomaldehyde in salted fish snapper marinated with salt water for 60 minutes with a concentration of soaking 0% or a control that is, the concentration of 30% ie, and 50% are. It can be concluded that there are significant concentrations of salt water immersion on levels of formaldehyde in salted fish.